Consumer demand and traditional medicine prescription of bear products in Vietnam. (July 2019) - Davis, Elizabeth Oneita; Glikman, Jenny Anne; Crudge, Brian; Dang, Vinh; Willemsen, Madelon; Nguyen, Trang; O'Connor, David; Bendixsen, Tuan
Abstract: The illegal trade in wildlife products is a major driver of the global biodiversity crisis. Trade in wildlife products is driven by consumer demand; however, consumer's motivations are often poorly understood. In this study, we use mixed social science approaches to understand the motivations driving consumers of bear products for medicine in Vietnam, and of traditional medicine practitioners who may be influencing consumers. In addition, we provide current information about the ways bear products are used in the two largest cities of Vietnam: Hanoi and Ho Chi Minh City. We found that bear products are still used widely in Vietnam, despite their use being prohibited since 2006. We directly estimated use at 45% of the sample of consumers for Hanoi, and 18% for consumers in Ho Chi Minh City. However, bear products are used differently between the two cities, with Hanoians more likely to take bear medicine products to treat an ailment, versus Ho Chi Minh City, where it is taken as a daily tonic. We also found that some traditional medicine practitioners in Vietnam are continuing to prescribe bear products, despite medicinal prescription of bear bile being made illegal, and availability of traditional medicine herbal alternatives. Generally, use of bear products appears to still be widely acceptable in the country, indicating a need for changing the social norms of bear product consumption. The insights gathered here will be beneficial to conservation managers working in Vietnam and throughout the Southeast Asia region, and will be particularly informative for developing and implementing demand reduction campaigns.